The Vietnam War in American Childhood - Rhodes, Joel P., 1967- (Book collections on Project MUSE., 2019)
For American children raised exclusively in wartime -- that is, a Cold War containing monolithic communism turned hot in the jungles of Southeast Asia -- and the first to grow up with televised combat, Vietnam was predominately a mediated experience. Walter Cronkite was the voice of the conflict and grim, nightly statistics the most recognizable feature. In seeing the Vietnam War through the eyes of preadolescent Americans, the book suggests broader developmental implications from being socialized to the political and ethical ambiguity of Vietnam. Although youth during World War II retained with clarity into adulthood many of the proscriptive patriotic messages about U.S. rightness, why-we-fight, heroism, or sacrifice they were indoctrinated with during the war years, conversely, Vietnam tended to breed childhood ambivalence, but not necessarily of the hawk and dove kind. This unique perspective on Vietnam continues to complicate adult notions of militarism and warfare, while generally lowering expectations of American leadership and the presidency